Policies to promote growth and economic efficiency in Mexico - Javier Arias; Oliver Azuara; Pedro Bernal; James Joseph Heckman; Cajeme Villarreal (Institute for the Study of Labor (IZA), 2010)
This paper discusses the problems facing the Mexican economy. It operates under a heavy burden of monopoly and regulation. We focus on two issues that should receive more attention in discussions of Mexican policy. (1) The family is under stress in Mexico and this retards the growth of skills of workforce. (2) The informal sector is large, mostly due to the heavy burden of monopoly and regulation. We find little evidence that the introduction of social protection programs for workers outside the formal sector have promoted the growth of the informal sector.
Keywords: J13; L51; O17; 330; Mexico; family policy; informality; regulation; Informeller Sektor; Familiensoziologie; Sozialer Wandel; Regulierung; Monopol; Wirtschaftswachstum; Mexiko